PENGARUH METODE PERMAINAN CERDAS CERMAT TERHADAP PARTISIPASI BELAJAR ANAK SEKOLAH MINGGU HORONG 3 DI DESA GURGUR AEK RAJA - Ayu Simanjuntak; Vidya Zati (STKIP Subang, 2026)
This study aims to analyze the influence of the quiz bowl (cerdas cermat) game method on the learning participation of Horong 3 Sunday School children in Gurgur Aek Raja Village, Samosir Regency, North Sumatra. The background of this research is initiated by the low level of children's learning participation, which is characterized by passive attitudes, a lack of focus, and the dominance of the lecture method. This study employed a quantitative approach with a Pre-Experimental One-Group Pretest-Posttest Design involving 30 children selected through a total sampling technique. Data were collected using a learning participation questionnaire (30 items, α = 0.974) and observation sheets for the implementation of the method. The Shapiro-Wilk normality test results indicated that the data were normally distributed (pretest p = 0.793; posttest: p = 0.857). Hypothesis testing using the Paired Samples T-Test yielded a value of tcount = 57.616 > ttable = 2.045 with a significance level of p < 0.001. The average participation score increased from 58.77 (48.9%, low category) to 100.17 (83.4%, high category). These findings prove that the quiz bowl game method has a significant influence on increasing children's learning participation in non-formal religious education.